Use of Radical Oxygen Species Scavenger Nitrones to Treat Oxidative Stress-Mediated Hearing Loss: State of the Art and Challenges - Varela-Nieto, Isabel; Murillo-Cuesta, Silvia; Rodríguez-de la Rosa, Lourdes; Oset-Gasque, María Jesús; Marco-Contelles, José (Frontiers in Cellular Neuroscience, 2021)
Nitrones are potent antioxidant molecules able to reduce oxidative stress by trapping reactive oxygen and nitrogen species. The antioxidant potential of nitrones has been extensively tested in multiple models of human diseases. Sensorineural hearing loss has a heterogeneous etiology, genetic alterations, aging, toxins or exposure to noise can cause damage to hair cells at the organ of Corti, the hearing receptor. Noxious stimuli share a battery of common mechanisms by which they cause hair cell injury, including oxidative stress, the generation of free radicals and redox imbalance. Therefore, targeting oxidative stress-mediated hearing loss has been the subject of much attention. Here we review the chemistry of nitrones, the existing literature on their use as antioxidants and the general state of the art of antioxidant treatments for hearing loss.